2015
DOI: 10.1007/s00436-015-4721-7
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of pathogenic free-living amoeba from surface and tap water of Shiraz City using morphological and molecular methods

Abstract: Free-living amoebae (FLA) are the most abundant and widely distributed protozoa in the environment. An investigation was conducted to determine the presence of free-living amoebae (FLA), Acanthamoeba and Vermamoeba in waterfronts of parks and squares and tap water of Shiraz City, Iran. FLA are considered pathogenic for human. These ubiquitous organisms have been isolated from different environments such as water, soil, and air. Eighty-two water samples were collected from different places of Shiraz City during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…In this survey, based on the morphological assessment, about half of the water samples were identified as the Acanthamoeba spp. Also, all of the positive samples were reconfirmed by the molecular method as Acanthamoeba spp, the obtained results in the present study give further evidence of the presence of Acanthamoeba spp in the surface waters exist in Iran which is in accordance with other investigations worldwide [6,15,17,22,[41][42][43].…”
Section: The Molecular Identificationsupporting
confidence: 91%
See 2 more Smart Citations
“…In this survey, based on the morphological assessment, about half of the water samples were identified as the Acanthamoeba spp. Also, all of the positive samples were reconfirmed by the molecular method as Acanthamoeba spp, the obtained results in the present study give further evidence of the presence of Acanthamoeba spp in the surface waters exist in Iran which is in accordance with other investigations worldwide [6,15,17,22,[41][42][43].…”
Section: The Molecular Identificationsupporting
confidence: 91%
“…There are a few reports available regarding the presence of Acanthamoeba spp in different water sources in Iran [12,13,15,22,24,40]. The results of previous studies in Iran showed that an increasing rate, in addition to being in the Acanthodea keratitis, was also in an undistinguished encephalitis in the immunocompromised patients [5,19,20,22]. Accordingly, the isolation and identification of Acanthamoeba spp in water sources may play an important role in the prevention and control of the above mentioned serious problems.…”
Section: The Molecular Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Vermamoeba vermiformis is one of the most common FLA to have been isolated from different water systems (Rhoads et al 2015;Montalbano Di Filippo et al 2015;Lu et al 2015;Armand et al 2016). It is also frequently recovered from hospital water networks as shown by several authors (Rohr et al 1998;Thomas et al 2006;Ovrutsky et al 2013;Pagnier et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of putative genes with a size equal to or greater than 100 amino acids (aa) was estimated to be 90.3% (20,299 genes). Out of all the predicted genes, 67.9% (15,266) were non-ORFan genes and 32.1% (7,217) were ORFans (i.e. they have no homologs in the NCBI GenBank protein sequence database (nr)) ( Table 1).…”
mentioning
confidence: 99%